Ação protetora da Carya illinoensis sobre a toxicidade induzida por ciclofosfamida em ratos - Benvegnú, Dalila Moter (2010)
Cyclophosphamide (CP) is an alkylating agent widely used in anticancer and immunosuppression therapy. Like other chemotherapies, this drug can induce damage in healthy tissues, generating multiple organ toxicity. The study of natural substances able to prevent or reduce the toxicity induced by the chemotherapy is very important. Pecan nut shell (Carya illinoensis) is a vegetal by-product with low cost and elevated antioxidant potential and therefore can be considered a promissory substance. The aim of this study was to verify whether the cited antioxidant protects against multiple tissue damage induced by CP. Wistar rats received water or pecan shell aqueous extract (AE - 5%) ad libitum in place of drinking water up to the end of the experiment. On day 30, half of each group received a single administration of vehicle or CP 200 mg/kg-ip. After 7 days, the animals were sacrificed by exsanguination. The blood was collected to obtain plasma and erythrocytes. Vital tissues as heart, liver, kidney, testis and bladder were removed. The occurrence of oxidative stress (OS) was observed through the determination of lipid peroxidation (LP), measured by the thiobarbituric acid reactive substances (TBARS) formation and reduced glutathione (GSH) in all removed tissues, the enzyme catalase (CAT) in the heart, liver, kidney and testis, the enzyme superoxide dismutase (SOD) in the testis and the plasmatic vitamin C (VIT C) levels. Furthermore, the testicular function was evaluated by the enzyme lactate deydrogenase (LDH) and the macroscopic and histopathological analysis of the bladder was carried out. Results demonstrated that the CP treatment increased TBARS and decreased GSH levels in all studied tissues. Moreover, the activities of SOD in the testis and CAT in the heart were increased. However, in the other organs, the activity of the latter was diminished. The testicular LDH and plasmatic VIT C levels were also decreased. Finally, the bladder of the CP treated rats showed dark color and various histological alterations, such as thickening of the lines, hemorrhage, edema, leukocyte infiltration and vascular proliferation. The co-treatment with AE was able to prevent the TBARS increase and GSH depletion in all tissues, except heart and plasma, respectively. The extract also prevented changes in the testicular SOD and CAT activity in all organs, except the kidney. Besides, the extract prevented alteration in plasmatic VIT C and testicular LDH as well as various visual and histological changes in the rat bladder. These findings provided important evidences of the protective effect of pecan shell AE against the general organic toxicity induced by CP. Therefore, this natural substance may be considered to minimize adverse effects related with this chemotherapy, improving the life quality of patients who need to use this type of drug.